Vivências das infâncias camponesas e educação do campo: perspectivas na EMEIEF Senhor do Bonfim - Cabral, Edmilson da Silva (2024)
The following dissertation, linked to the Popular Education line of research of the Federal University of Paraíba’s Postgraduate Program in Education, analyzed the specificities of childhood experiences through the lenses of the pedagogical practices developed with and for children on rural schools. Conceptually, we consider the child as a social subject with full rights and childhood as a social category (which in the rural field is characterized by its heterogeneity and multiplicity of experiences). We employed the methodology of empirical field research with a qualitative approach, focusing on the EMEIEF Senhor do Bonfim school in the township of Sapé (located on the state of Paraíba in Brazil’s Northeastern region). This school is situated in the Rainha dos Anjos settlement, an area settled by the Landless Workers' Movement (MST) and offers classes for all educational stages connected to childhood, from kindergarten and preschool (2 to 5 years-old) up to elementary school (6 to 10 years-old, grades 1 through 5). Our collaborating subjects included the children enrolled in the grade 1 and 2 multigrade classes and their teacher, comprising a total of twelve (12) children and one (01) professional educator. We employed the methods of observation, semi structured interviews, and thematic workshops (including drawing, painting, and journaling with the children). Data interpretation and analysis were based on the theoretical perspective of Childhood Sociology as defined by Corsaro (2011), Sarmento (2020), Arenhart (2007), Antônio and Tavares (2013, 2019). From this foundation, this study allowed us to categorize the pedagogical practices developed with children in rural schools and identify the viewpoints of rural children on their childhood experiences regarding school and rural life. In conclusion, this research shows that these concepts contribute to make the rural school a space of opportunities for the full range of childhood experiences, through an educational process based on play-based games, interactions, and contexts suitable for the rural peoples’ realities.